2017
DOI: 10.4028/www.scientific.net/kem.745.91
|View full text |Cite
|
Sign up to set email alerts
|

Use of Collagen Scaffolds in Conjunction with NPWT for the Care of Complex Wounds: Clinical Report

Abstract: Open wounds treatment is very often a challenge for both the physician and patient. They require long term complex treatment with surgical debridement, dressing changing, additional therapies including expensive medication, with a high risk of failure. The most difficult to treat are the diabetic wounds and those that are associated with advanced arterial disease. In these special cases, the peripheral vascularization is severely impaired and the complications are imminent. Sixteen patients were selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Our described combination technique of ORC/collagen/ silver and NPWT was described earlier in a similar fashion. 21,22 In these two studies, the use of collagen had been proposed to accelerate the growth of granulation tissue by providing a bio-scaffold for the retention of fibroblasts to lay new tissue, and NPWT stimulated healing by increasing local tissue perfusion, hence facilitating adherence of the tissue layers in the wound bed. 18,19 These studies reported reduction in wound area and volume upon addition of ORC/collagen dressings to conventional NPWT in complex wounds.…”
Section: "Seed and Soil" Theory Of Wound Healingmentioning
confidence: 99%
“…Our described combination technique of ORC/collagen/ silver and NPWT was described earlier in a similar fashion. 21,22 In these two studies, the use of collagen had been proposed to accelerate the growth of granulation tissue by providing a bio-scaffold for the retention of fibroblasts to lay new tissue, and NPWT stimulated healing by increasing local tissue perfusion, hence facilitating adherence of the tissue layers in the wound bed. 18,19 These studies reported reduction in wound area and volume upon addition of ORC/collagen dressings to conventional NPWT in complex wounds.…”
Section: "Seed and Soil" Theory Of Wound Healingmentioning
confidence: 99%
“…The most frequent subdrape materials used in modern NPWT systems are foams, with the black polyurethane (PU) foam being the first, followed by “white” and then “green” foams. Other nonfoam materials such as cotton gauze are used, and a variety of materials are being developed and tested for possible incorporation into vacuum-assisted NPWT systems 3–11…”
Section: Introductionmentioning
confidence: 99%
“…Other nonfoam materials such as cotton gauze are used, and a variety of materials are being developed and tested for possible incorporation into vacuum-assisted NPWT systems. [3][4][5][6][7][8][9][10][11] Research in vacuum-assisted NPWT technologies has also evaluated subdrape materials with the intention of expanding the clinical utility of this component of the NPWT system. 11 Th e fi rst example comprised a silver-impregnated version of the black foam designed to provide antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations